The Legal Responsibility of Government in The Implementation of Sustainable Development Policies: A Normative Juridical Study on The Role of Bureaucracy In Supporting The Achievement of Sustainable Development Goals (SDGs) In Indonesia - Anak Agung Gede Agung Indra Prathama; Cokorda Gede Swetasoma; Kadek Ary Purnama Dewi (Journal Equity of Law and Governance, 2026)
Sustainable development is a development paradigm that emphasizes the balance among economic, social, and environmental dimensions, aiming to fulfill the needs of the present generation without compromising the ability of future generations to meet their own needs. This study aims to identify the legal norms underpinning government obligations, evaluate the implementation of bureaucratic roles based on the prevailing legal framework, and examine the juridical and institutional obstacles that hinder the effective implementation of the Sustainable Development Goals (SDGs). The legal issues addressed in this research include: (1) What is the nature of the legal responsibility of the Indonesian government in implementing sustainable development policies? (2) How does the bureaucracy contribute to supporting the achievement of SDGs from a normat ive legal perspective? (3) What juridical and institutional challenges do the bureaucracy face in executing the SDGs, and what legal solutions can be proposed? This study employs a normative juridical approach, focusing on the analysis of positive legal norms, including national legislation, constitutional provisions, and binding policy documents related to sustainable development implementation. The approach is complemented by a review of relevant literature and international legal instruments pertaining to the SDGs agenda. The findings indicate that, normatively, the Indonesian government holds a clear and binding legal obligation to realize the principles of sustainable development. However, the effectiveness of policy implementation is significantly in fluenced by the bureaucracy’s performance, which is expected to be responsive, transparent, and accountable. Therefore, bureaucratic reform grounded in the principles of good governance is an essential prerequisite to support the achievement of sustainable development goals in Indonesia.